Population structure and Aflatoxin production by Aspergillus Sect. Flavi from maize in Nigeria and Ghana - Perrone, G.; Haidukowski, M.; Stea, G.; Epifani, F.; Bandyopadhyay, Ranajit; Leslie, J.; Logrieco, A. (Elsevier, 2014)
Aflatoxins are highly toxic carcinogens that contaminate crops worldwide. Previous studies conducted inNigeria and Ghana found high concentrations of aflatoxins in pre- and post-harvest maize. However,little information is available on the population structure of Aspergillus Sect. Flavi in West Africa. Wedetermined the incidence of Aspergillus Sect. Flavi and the level of aflatoxin contamination in 91 maizesamples from farms and markets in Nigeria and Ghana. Aspergillus spp. were recovered from 61/91 maizesamples and aflatoxins B1 and/or B2 occurred in 36/91 samples. Three samples from the farms alsocontained aflatoxin G1 and/or G2. Farm samples were more highly contaminated than were samples fromthe market, in terms of both the percentage of the samples contaminated and the level of mycotoxincontamination. One-hundred-and-thirty-five strains representative of the 1163 strains collected wereidentified by using a multilocus sequence analysis of portions of the genes encoding calmodulin, btubulinand actin, and evaluated for aflatoxin production. Of the 135 strains, there were 110 e Aspergillusflavus, 20 e Aspergillus tamarii, 2 e Aspergillus wentii, 2 e Aspergillus flavofurcatus, and 1 e Aspergillusparvisclerotigenus. Twenty-five of the A. flavus strains and the A. parvisclerotigenus strain were the onlystrains that produced aflatoxins. The higher contamination of the farm than the market samples suggeststhat the aflatoxin exposure of rural farmers is even higher than previously estimated based on reportedcontamination of market samples. The relative infrequency of the A. flavus SBG strains, producing smallsclerotia and high levels of both aflatoxins (B and G), suggests that long-term chronic exposure to thismycotoxin are a much higher health risk in West Africa than is the acute toxicity due to very highlycontaminated maize in east Africa.